PIIS Students' Perceptions at Tanjungpura University on the Role of Artificial Intelligence in Developing Academic Speaking Skills - Anzani, Nazwa; Barella, Yusawinur (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
The rapid global adoption of Artificial Intelligence (AI) has transformed higher education, necessitating research on its impact, particularly in social science fields. This study investigates the perception of 151 undergraduate students from the Social Sciences Education Department at Tanjungpura University towards the role of AI in developing Academic Speaking Skills. Employing a quantitative, descriptive survey design, the research utilizes the Technology Acceptance Model (TAM) framework, assessing Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Attitude Toward Using (ATT), and Behavioral Intention to Use (BITU). The findings indicate an overall positive and stable acceptance of AI (Overall Mean 2.895 on a 4 -point scale). Perceived Usefulness is the highest adoption driver (Mean 3.00), with students most strongly agreeing that AI is superior for brainstorming and finding ideas for presentations (Mean 3.26). However, the acceptance is critical and controlled: students showed lower confidence that AI automatically improves the overall quality of their final arguments (Mean 2.66). This discrepancy, alongside the lowest score in Behavioral Intention to Use (Mean 2.74), highlights a controlled integration approach. The study concludes that while AI is highly valued as a creative support tool, there is a crucial and urgent need to integrate mandatory AI Literacy programs into the curriculum to ensure students develop the critical skills necessary to review, adapt, and responsibly use AI output in academic discourse within Higher Education.